Treatment of Postpartum Metritis in Dairy Cattle (Medico Legal Update, 2021)
After delivery uterine function usually exposed by bacterial contamination of the uterine lumen. This studywas conducted on 21 cows of Holstein-Friesian breed, aged between 4-6 years, with parity of 2-4 timessuffered from postpartum metritis. The disease diagnosed according to the clinical symptoms and vaginalexamination. Animals divided into 3 equal groups. 1st group treated with PGF2? 20 mg/im., 2nd group treatedwith 2% lugol’s Iodine Intra Uterine, while the 3rd group treated with lotagen 2% I.U. The results showedthat the treatment with PGF2? give high efficacy rate 100% (7/7) than that with lugol’s Iodine 57% (4/7) andwith lotagen 71% (5/7). There was a significant difference (P?0.05) in treatment with PGF2? as comparedwith other treatments, it was concluded from this study that PGF2? give the best results in postpartummetritis treatment.